Penguatan Pendidikan Karakter melalui Pembelajaran Geografi Berbasis Nilai Sosial - Sukmawati Sukmawati; Sunimbar Sunimbar (Journal of Humanities, Social Sciences, and Education, 2025)
Character education is a fundamental aspect in forming a generation that is not only academically intelligent, but also moral and has a noble personality. Geography learning as part of social science has great potential in instilling social values ​​and character in students. This literature study aims to examine how Geography learning can be used as a vehicle to strengthen character education based on social values. This study uses a qualitative approach with a literature study method on relevant articles, journals, and books in the period 2019-2024. The results of the analysis show that Geography learning based on social values ​​is able to shape students' characters such as social empathy, tolerance, environmental responsibility, nationalism, and mutual cooperation. This learning also encourages students to understand the social and geospatial realities around them, as well as foster awareness of global issues such as climate change and social inequality. By strengthening the affective aspect in Geography learning, teachers play a strategic role in shaping students' personalities. With an integrative and contextual approach, Geography learning is not only a transfer of knowledge, but also a process of internalizing the noble values ​​of nationality and humanity. Therefore, innovation and development of Geography learning models are needed that are able to integrate character education systematically and sustainably.